2012
DOI: 10.1523/jneurosci.2810-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Cortical Subnetworks Differentially Connect Frontal Cortex to Parahippocampal Areas

Abstract: How information is manipulated and segregated within local circuits in the frontal cortex remains mysterious, in part because of inadequate knowledge regarding the connectivity of diverse pyramidal cell subtypes. The frontal cortex participates in the formation and retrieval of declarative memories through projections to the perirhinal cortex, and in procedural learning through projections to the striatum/pontine nuclei. In rat frontal cortex, we identified two pyramidal cell subtypes selectively projecting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 57 publications
5
99
1
Order By: Relevance
“…Intermingled L5 pyramidal neurons in the mPFC that project to distinct cortical and subcortical targets often have different morphological and physiological properties (Morishima and Kawaguchi, 2006;Dembrow et al, 2010;Morishima et al, 2011;Otsuka and Kawaguchi, 2011). We found that L2 pyramidal neurons in the mPFC also have distinct targets, including the BLA and cmPFC, consistent with recent anatomy (Hirai et al, 2012). However, we observed minimal differences in dendritic morphology and intrinsic physiology of CA and CC neurons.…”
Section: Reciprocal Circuits Involving L2 Pyramidal Neuronssupporting
confidence: 88%
See 1 more Smart Citation
“…Intermingled L5 pyramidal neurons in the mPFC that project to distinct cortical and subcortical targets often have different morphological and physiological properties (Morishima and Kawaguchi, 2006;Dembrow et al, 2010;Morishima et al, 2011;Otsuka and Kawaguchi, 2011). We found that L2 pyramidal neurons in the mPFC also have distinct targets, including the BLA and cmPFC, consistent with recent anatomy (Hirai et al, 2012). However, we observed minimal differences in dendritic morphology and intrinsic physiology of CA and CC neurons.…”
Section: Reciprocal Circuits Involving L2 Pyramidal Neuronssupporting
confidence: 88%
“…As in other cortical areas, these projection neurons are well known to have distinct properties, including dendritic morphology, intrinsic physiology, and synaptic connectivity (Hattox and Nelson, 2007;Le Bé et al, 2007;Brown and Hestrin, 2009). In the mPFC, L2 pyramidal neurons also send long-range outputs, including to both the BLA and cmPFC (Gabbott et al, 2005;Hirai et al, 2012). These projection neurons thus appear well positioned to help govern the cognitive and emotional functions of the mPFC.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed the same form of dopamine-dependent changes of corticostriatal inputs as above for both the dMSNs and iMSNs. It might appear odd to make such an assumption, given the distinct properties of the D 1 Rs and D 2 Rs that are separately expressed in dMSNs and iMSNs (Gerfen and Surmeier, 2011). However, according to our hypothesis (Fig.…”
mentioning
confidence: 68%
“…However, again, afferent stimulation applied in that study possibly caused phasic dopamine release, and its effect was possibly masked by bath application of D 2 agonist [possible occurrence of such a masking in vivo has been discussed previously (Klein et al, 2007)]. Potential difference between bacterial artificial chromosome transgenic mice and wild-type animals (Bagetta et al, 2011;Kramer et al, 2011;Nelson et al, 2012) may also need to be carefully considered.Overall, our assumption on plasticity could be in line with, or at least not inconsistent with, several experimental results as we explained above, but there remain divergences and limitations that need to be clarified in the future. An important limitation of our model, which would especially affect plasticity, is that it modeled neural activity as a continuous variable and did not model individual spike timings.…”
mentioning
confidence: 79%
“…We searched for changes at synapses that target pyramidal cells (PCs) in dmPFC layer V. These cells belong to dmPFC major output neurons. They innervate multiple targets including the cortex, amygdala, striatum, thalamus, brainstem nuclei and spinal cord (Gabbott et al, 2005;Hirai et al, 2012;Shepherd, 2013). As their apical dendrites extend towards the superficial layer of dmPFC, the layer V PC are positioned to integrate information from all cortical layers by receiving inputs from local neurons and remote projections from all over the brain (Ramaswamy and Markram, 2015).…”
Section: Introductionmentioning
confidence: 99%